Transformasi Wilayah Kota Mandiri pada Kawasan Permukiman (Studi Kasus : Perkampungan Karawaci, Kabupaten Tangerang, Provinsi Banten) - Wahyu Ika Nur Fitriyani; Arfani Priyambodo; Joseph Edward Timothy Siahaan; Misbahul Hayat Fathul Husni (Jurnal Pembangunan Wilayah dan Kota, 2021)
The increasing population that occurs in the metropolis of Indonesia often causes problems with the structure of urban space utilization. It’s triggered by the phenomenon of urban sprawl that occurs in the outskirts of Jakarta, especially Tangerang, causing a transformation of the landscape. The existence of Lippo Karawaci which is supported by road accessibility and supporting facilities and infrastructures encourages the growth of a new city center titled independent city. The development of independent cities has the potential to change the structure of urban spaces that cause changes in the pattern of development of residential areas, especially in rural areas. This research emphasizes the condition of distance in the residential areas in Karawaci, namely Kampung Bencongan, Binong Village, Dadap Village, and Kampung Kelapa Dua as icons of traditional settlements associated with the city center. The purpose of this research is to know the transformation of land use and analyze spatial patterns of independent urban settlements in Karawaci Village. In conducting the analysis, the method used is descriptive spatial analysis with NNA (Nearest Neighbor Analysis) method to produce the pattern of settlements formed and land use transformation in residential areas through ArcMap 10.8 software. The required data was obtained through participatory mapping using the Google Earth platform for the 2003-2020 recording year as well as field observations by comparing the conditions of village distance to independent cities. The results showed an increase in settlement area of 11.4% (2.51 ha) in Binong Village, 14.2% (2.08 ha) in Dadap Village, 15.7% (4.84 ha) in Kampung Kelapa Dua, and 9.7% (3.67 ha) in Kampung Bencongan from 2003 to 2020. Spatial patterns formed in residential areas in Karawaci Village show that the closer the residential area with an independent city center will form a cluster settlement pattern. Meanwhile, the further the residential area from the city center independently will form a pattern of random settlements. So, it can be concluded that the transformation of the city space structure with the development of independent cities increases the area of settlements and forms different patterns of settlements to the city center.